SYMBOLIC CONVERGENCE IN THE INDEPENDENT MEN OF FLOBAMORA COMMUNITY - Killa, William Gilbert; Andung, Petrus Ana; Jelahut, Felisianus Efrem (ASPIRATION Journal, 2023)
This research aims to analyze the fantasy themes that are formed and build cohesiveness and describe the symbolic convergence that is formed in the Independent Men of Flobamora community. The theory used is symbolic convergence theory. This research is a qualitative descriptive study with a fantasy theme analysis method, which uses data collection techniques using observation, focus group discussions, interviews, and document study. The research results show that the Independent Men of Flobamora community in building its cohesiveness occurs in a continuous process. starting from the process of forming a collective identity which is the basis for creating fantasy themes. The process of forming a collective identity and cohesiveness begins with the stigma and discrimination experienced by members of the Independent Men of Flobamora community. This experience is shared in a message exchange process which then experiences message dramatization followed by the creation of symbolic interactions that lead to symbolic convergence. The dramatized message gets responses from other participants which form a series of fantasies.